2018
DOI: 10.1182/blood-2017-09-804419
|View full text |Cite
|
Sign up to set email alerts
|

Gene therapy with adeno-associated virus vector 5–human factor IX in adults with hemophilia B

Abstract: Gene therapy for hemophilia B aims to ameliorate bleeding risk and provide endogenous factor IX (FIX) activity/synthesis through a single treatment, eliminating the requirement for FIX concentrate. AMT-060 combines an adeno-associated virus-5 (AAV5) vector with a liver-specific promoter driving expression of a codon-optimized wild-type human FIX gene. This multinational, open-label study included 10 adults with hemophilia B (FIX ≤2% of normal) and severe-bleeding phenotype. No participants tested positive for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
293
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(324 citation statements)
references
References 28 publications
9
293
2
2
Order By: Relevance
“…Some discrepancies between assays and assay reagents notwithstanding, it was agreed that the haemophilia community should establish a minimally acceptable factor level and a minimum durability of treatment, for gene therapy to be considered successful. Several studies have demonstrated that a reduction in bleeding and factor use can be achieved with FIX expression levels of <10%; however, a minimal acceptable level still needs to be determined. Subsequent to the round table, the FDA issued draft guidelines specifying that factor levels may be utilized as the primary endpoint for breakthrough therapy approval, but ABR was proposed as the primary endpoint for the regular approval process .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some discrepancies between assays and assay reagents notwithstanding, it was agreed that the haemophilia community should establish a minimally acceptable factor level and a minimum durability of treatment, for gene therapy to be considered successful. Several studies have demonstrated that a reduction in bleeding and factor use can be achieved with FIX expression levels of <10%; however, a minimal acceptable level still needs to be determined. Subsequent to the round table, the FDA issued draft guidelines specifying that factor levels may be utilized as the primary endpoint for breakthrough therapy approval, but ABR was proposed as the primary endpoint for the regular approval process .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we have seen the introduction of non‐factor therapies, including gene therapy, reach late phase clinical trials and the market . There are currently several ongoing clinical trials for both FVIII and FIX gene therapy, and barring unforeseen safety or efficacy issues, it is expected that at least 1‐2 will obtain regulatory approval in the next few years.…”
Section: Introductionmentioning
confidence: 99%
“…1 Importantly, hemoglobin appears to be the strongest predictor of CBF and OEF in this report and across all studies, potentially calling into question current transfusion practice guidelines that only consider posttransfusion hemoglobin S levels. ASE and other advanced neurovascular imaging techniques will be essential to determine the optimal hemoglobin level for cerebral protection in SCD patients and the role of hemoglobin S in cerebrovascular toxicity.…”
mentioning
confidence: 72%
“…106 When a higher dose was given (2 × 10 13 vg/kg) to another patient cohort, the FIX expression levels improved to almost 7%. Approximately 4% of FIX expression levels was achieved in the patients that received a dose of 5 × 10 12 vg/kg of the AMT-060 vector.…”
Section: Haemophilia Bmentioning
confidence: 96%